Double-controlled release of poorly water-soluble paliperidone palmitate from self-assembled albumin-oleic acid nanoparticles in plga in situ forming implant - Yu, Yongjun; Ngo, Hai V.; Jin, Gang; Tran, Phuong H.L.; Tran, Thao T.D.; Nguyen, Van Hong; Park, Chulhun; Lee, Beom Jin (International Journal of Nanomedicine, 2021)
Purpose: To investigate the effects of solvents on the formation of self-assembled nanoni-zation of albumin-oleic acid conjugates (AOCs) using a solvent exchange mechanism for the construction of in situ forming implants (ISFI). Methods: A poorly water-soluble drug, paliperidone palmitate (PPP), was chosen as the model drug. AOC was synthesized with the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) reaction. Dichloromethane, tetrahydrofuran, ethanol, N-methyl-2-pyrrolidone, dimethyl sulfoxide, and deionized water were selected to investigate the formation of self-assembled AOC nanoparticles (AONs). The volume ratios of organic solvents against water could determine the miscibility, injectability, and in situ nanonizing capability without aggregation. Results: As the polarity of the organic solvents increased, the AONs exhibited a spherical shape, and the larger the volume of the solvent, the smaller the size of the AONs. To use AOC in ISFI for controlled release of PPP, poly(d,l-lactide-co-glycolide) (PLGA) was combined with the AOC in 2 mL of N-methyl-2-pyrrolidone and water solution (1.8/0.2 ratio). The release rates of all formulations exhibited similar curve patterns overall but were more controlled in decreasing order as follows: AOC, PLGA, and AOC/PLGA for 14 days. Conclusion: A combined formulation of AOC and PLGA was found to effectively control the initial burst release of the drug.
Keywords: Albumins; Delayed-Action Preparations; Dimethyl Sulfoxide; Drug Implants; Ethanol; Nanoparticles; Oleic Acid; Paliperidone Palmitate; Polylactic Acid-Polyglycolic Acid Copolymer; Pyrrolidinones; Solubility; Solvents; Spectroscopy, Fourier Transform Infrared; Water; Albumin-oleic acid conjugate; Controlled release; In situ forming implant; Self-assembled nanonization; Solvent exchange; Solvent type